1974
DOI: 10.1083/jcb.63.2.550
|View full text |Cite
|
Sign up to set email alerts
|

Microtubular Organization in Elongating Myogenic Cells

Abstract: Microtubule organization has been studied in serially sectioned myogenic cells in the tail muscle regeneration blastema of Rana pipiens tadpoles. In mesenchymal cells and in some premyoblasts, microtubules radiate from centriolar satellites in a cell center, while in more mature myoblasts a n d myotubes the centrioles no longer appear to serve as organizing centers for microtubules. In all elongate, fusiform myogenic cells, the microtubules are predominately oriented in the longitudinal axis of the cell. Count… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
58
1

Year Published

1975
1975
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(63 citation statements)
references
References 46 publications
4
58
1
Order By: Relevance
“…Previous studies on the equilibrium nature of microtubule polymerization suggested a mechanism of condensation-polymerization characterized by distinct phases of nucleation and growth (17,22). Since purified tubulin subunits were capable of rapid addition onto preexisting microtubule fragments and because HMW-free tubulin did polymerize slowly, these results and the work of Kirschner et al (23) (26) and in developing myoblasts (5) indicate that these arrays consist primarily of short, overlapping tubule fragments. These studies suggest that the structural integrity of the overall microtubule array requires lateral interaction between paraxial tubules.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Previous studies on the equilibrium nature of microtubule polymerization suggested a mechanism of condensation-polymerization characterized by distinct phases of nucleation and growth (17,22). Since purified tubulin subunits were capable of rapid addition onto preexisting microtubule fragments and because HMW-free tubulin did polymerize slowly, these results and the work of Kirschner et al (23) (26) and in developing myoblasts (5) indicate that these arrays consist primarily of short, overlapping tubule fragments. These studies suggest that the structural integrity of the overall microtubule array requires lateral interaction between paraxial tubules.…”
Section: Discussionsupporting
confidence: 68%
“…For some of these functions microtubule-associated elements such as crossbridges have been postulated (2,3), and structural components attached to microtubules have been observed in neurons (4), myoblasts (5), and the mitotic spindle (6,7). Although a microtubule sidearm which produces the force for axonemal motility has been isolated from cilia and flagella (8), in no case have the structural components observed on cytoplasmic microtubules been characterized biochemically or had their exact functions defined.…”
mentioning
confidence: 99%
“…In general, fibroblasts in culture contain abundant microtubules that are rapidly destroyed by such drugs or mitotic inhibitors as colchicine, Colcemid, and the vinca alkaloids (25-27). In addition, the correlation between elongation of eukaryotic cells and alignment of longitudinally oriented microtubules has been observed in most of the cell systems studied (28)(29)(30). as we have shown in this study, parallel conditions that preserve extensive elongated microtubules in CHO cells (21-23) inhibit synchronous rhythmic contractions of myocytes in culture.…”
Section: Discussionmentioning
confidence: 63%
“…10). Similar distribution patterns have been observed in skeletal muscle fibers (2,12,21,32,33) and in cardiac muscle cells (4,8,19,34). Goldstein and Entman (8) have also described MTscoiled in a helical fashion encircling myofibrils in cardiac muscle cells, but no such arrangement could be detected in our materials.…”
Section: Discussionmentioning
confidence: 47%
“…MTsare remarkably abundant in developing muscle cells (1,5,32,33). Thus much attention has been paid to the role of MTsin myogenesis.…”
mentioning
confidence: 99%